Evaluation of Panicle Exsertion and Identification of QTL for Long Panicle Neck in Single-segment Substitution Lines of Wild Rice - Jiamei MOU; Chengxia LI; Rui TANG; Yanjie LIU; Xingxin DAI; Xuelin FU (Guangdong nongye kexue)
【Objective】The phenomenon of panicle enclosure in rice is one of the important factors affecting the grain yield. Panicle exsertion of the wild rice species is generally in good state. In this study, by using the single-segment substitution lines (SSSLs) of Oryza meridionalis and O. barthii developed in our laboratory, the trait of panicle exsertion was investigated and the QTLs controlling panicle exsertion were identified, in order to lay a foundation for further cloning of the elite genes for panicle exsertion from wild rice, and to provide the genetic resources for the molecular breeding of the panicle exsertion in rice.【Method】Taking P < 0.01 as the criterion for significant difference, the SSSLs with significant longer panicle neck than that of HJX74 were screened out. Meanwhile, the controlling QTLs located in the interval of the substituted segments were identified, and their additive effects and phenotypic contribution rates of the QTLs were evaluated.【Result】A total of 4 stably expressed QTLs (qPEm5-1, qPEm5-2, qPEm8-1, and qPEm10-1) were identified in the SSSLs of O. meridionalis. The average additive effect values were in the range of 1.64-2.19 cm, respectively, and the phenotypic contribution rates of the additive effects were in the range of 114.53%-347.98%. In addition, a total of 11 stably expressed QTLs (qPEb1-1, qPEb1-2, qPEb1-3, qPEb2-1, qPEb3-1, qPEb3-2, qPEb4-1, qPEb5-1, qPEb6-1, qPEb7-1, and qPEb10-1) were identified in the SSSLs of O. barthii. Their average additive effect values were in the range of 1.74-4.08 cm, respectively, and the phenotypic contribution rates of the additive effects were 107.82%~481.80%. Among the QTLs of the two wild rice species, it was found that qPEm1-1 and qPEb1-1, qPEm1-1 and qPEb7-1, and qPEm10-1 and qPEb10-2 had the overlapping interval, respectively. It was implied that there probably have the same QTLs or alleles controlling the long panicle neck in the overlapping intervals of the two donor wild rice SSSLs. Moreover, three QTLs, qPEm5-1, qPEb5-1, and qPEb6-1 were considered as novel QTLs in this study, and their favorable alleles with positive effects were from the donor wild rice.【Conclusion】In this study, the panicle exsertion of the SSSLs of O. meridionalis and O. barthii were investigated in multiple seasons, and a total of 15 stably expressed QTLs for long panicle neck were identified. Among them, 3 novel QTLs were found. The results will lay a foundation for both further cloning and functional analysis of panicle exsertion genes from wild rice and molecular breeding for the panicle exsertion in rice.